2022
DOI: 10.3390/ijerph19106085
|View full text |Cite
|
Sign up to set email alerts
|

Association of Daily Exposure to Air Pollutants with the Risk of Tuberculosis in Xuhui District of Shanghai, China

Abstract: Previous studies have suggested that air pollutant exposure is related to tuberculosis (TB) risk, but results have not been consistent. This study evaluated the relation between daily air pollutant exposure and TB incidence in Shanghai from 2014 to 2019. Overall, there were four pollutants that were positively related to the risk of new TB cases. After a 5 μg/m3 increase, the maximum lag-specific and cumulative relative risk (RR) of SO2 were 1.081, (95% CI: 1.035–1.129, lag: 3 days) and 1.616 (95% CI: 1.119–2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Begg’s test, p = 1. Likewise, Xiong et al 46 reported an association (RR = 3.10, 95% CI: 1.10–8.79) for a 50 µg/m 3 increase in PM 2.5 concentration. The study by Lai et al 32 (RR = 1.39, 95% CI: 0.95–2.03) which was cohort in design did not find a significant association.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Begg’s test, p = 1. Likewise, Xiong et al 46 reported an association (RR = 3.10, 95% CI: 1.10–8.79) for a 50 µg/m 3 increase in PM 2.5 concentration. The study by Lai et al 32 (RR = 1.39, 95% CI: 0.95–2.03) which was cohort in design did not find a significant association.…”
Section: Resultsmentioning
confidence: 89%
“…3 ) 31 , 34 , 37 . However, Xiong et al 46 (RR = 1.8, 95% CI: 1.11–2.91) reported a significant association for a 5 µg/m 3 increase in NO 2 concentration.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations